Sports injuries with special reference to soccer: Causes, consequences and prevention strategies - Chaterjee, S.; Banerjee, N.; Bhattacharjee, S.; Santra, T.; Chatterjee, A.; Chatterjee, S.; Saha, B.; Mukherjee, S.; Manna, I. (American Journal of Sports Science, 2014)
Sports injury occurs during a sporting activity caused by overuse, direct impact, or the application of force that is greater than the body part can structurally withstand. Soccer is usually defined as a body contact outdoor game and therefore there is a chance of being injured by the opponents or due to not following proper playing rule or not using protective equipment. To maximize the health benefits of sports and exercise and to minimize the direct and indirect costs associated with injuries, developing and adopting injury prevention strategies is an important goal. Successful sports injury prevention programme requires successful implementation of effective interventions. This paper reviews the main mechanisms and risk factors for injuries to the head, groin, knee, ankle, muscle as well as the evidence supporting various strategies to prevent them. Approaches that have been shown to be successful include: (1) using protective equipment to reduce injury risk, (2) adopting the rules of play, and (3) specific exercise programmes developed to reduce injury risk.